FEASIBILITY STUDY OF THE RECEPTION FACILITY DEVELOPMENT OF TANJUNG PERAK BRANCH SURABAYA - Achmad Djamaludin; Benny Sukandari; Eko Krisdiono; Ali Mashudi (JOURNAL ASRO, 2019)
Presently, the rapidly increasing population growth has been shown to create the growing needs of sea transportation services, both for freight and passengers. The augmentation of sea transportation fleets causes the ever-increasing number of all types of ships and the vessel traffic congestion in many connected sailing lanes. The development of sea transportation media significantly affects the potency of sea pollution. Therefore, it requires an analysis of the development feasibility of the Reception Facility in Tanjung Perak Port Surabaya. The first analysis is by doing the evaluation of investment feasibility based on the law, market, technical and financial aspects. After that, the measurement is done by using the methods of Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), Average Rate of Return (ARR), Profitability Index (PI) and investment risk analysis. In this research, the gained NPV is about Rp. 431.257.167, PP value about 8 years 9 months 26 days, IRR 22,695%, ARR 30,32%, PI about 1,39, so the infrastructure investment program of Reception Facility in Tanjung Perak Port Surabaya is feasible to be carried out. Keywords: Feasibility Study, NPV, PP, IRR, ARR, PI, Investment Risk